1984
DOI: 10.1021/j150646a015
|View full text |Cite
|
Sign up to set email alerts
|

New simple functions to describe kinetic and thermodynamic effects of pressure. Application to Z-E isomerization of 4-(dimethylamino)-4'-nitroazobenzene and other reactions

Abstract: due to the differences in electronic configuration and thus differences in polarizabilities of these molecules. In this work, the polarizability differences are taken into account in the calculation of the adsorption potential as the mean polarizability and the polarizability ratio of the adsorbate molecule (ail/ais) assigned to each C force center of the molecule, derived from the corresponding molecular experimental data. The predicted s value for phenanthrene/anthracene adsorption on graphite is 1.44 when p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 2 publications
0
24
0
Order By: Relevance
“…Generally, the investigation of pressure effect on the rate of chemical reactions provides the important insights into the conformational changes during chemical reactions [14][15][16]. We previously demonstrated that the value of the activation free volume (ΔV ‡ ) for the thermal back reaction is an effective measure to evaluate the efficiency of the photochromic reaction in polymer matrix [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the investigation of pressure effect on the rate of chemical reactions provides the important insights into the conformational changes during chemical reactions [14][15][16]. We previously demonstrated that the value of the activation free volume (ΔV ‡ ) for the thermal back reaction is an effective measure to evaluate the efficiency of the photochromic reaction in polymer matrix [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…We have derived simple expressions for the pressure dependence of the reaction rate (eqn (12)] and the activation volume [eqn (15)] for ionic and polar reactions. We have assumed that the pressure dependence of the solvent volume and dielectric constant (reciprocal value), in the vicinity of the reactants, follows similar Tait equations, having the same B parameter.…”
Section: Discussionmentioning
confidence: 99%
“…In order to compare eqn (12) with experimental data we shall rewrite it in the following form : where Xl = P / B and X , = In (1 + P / B ) . A , is expected to be zero.…”
Section: Comparison With Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though Marcus cross-relation (7), was originally derived for the electron transfer reactions, it proved to be applicable to a wider range of processes, such as, for example, hydrogen transfer or SN2 reactions [13] . Therefore, one may expect that cross-relation (8) will also apply to a wider class of exchange reactions. there is no single cross-section that can be consistently assigned, the cylindrical model becomes ambiguous.…”
mentioning
confidence: 99%